Effect of Smear Layer on the Push-Out Bond Strength of Two Endodontic Biomaterials to Radicular Dentin - Lotfi, Mehrdad; Ghasemi, Negin; Rahimi, Saeed; Bahari, Mahmood; Vosoughhosseini, Sepideh; Saghiri, Mohammad Ali; Zand, Vahid (Iranian Endodontic Journal, 2013)
Introduction: This in vitro study was designed to evaluate the effect of smear layer removal on push-out bond strength of white mineral trioxide aggregate (WMTA) and calcium-enriched mixture cement (CEM). Materials and Methods: Dentin discs with 3 mm thicknesses were divided into 4 groups (n=15): group 1: irrigation of the canal with normal saline and filling with WMTA; group 2: irrigation with sodium hypochlorite (NaOCl) and ethylenediaminetetraacetic acid (EDTA), and then filling with WMTA; group 3: same as group 1 but the lumens were filled with CEM; group 4: same as group 2 but the lumens filled with CEM. The samples were incubated at 37°C for 3 days after wrapping in gauze pieces moistened with distilled water. The push-out bond strengths were then measured by the universal testing machine and the failure modes were examined under a stereomicroscope at 40× magnification. Data were analyzed using two-way ANOVA and post-hoc Tukey’s test for bond strength. Statistical significance was set at P<0.05. Results: The greatest and lowest mean standard deviation for push-out bond strength were observed for groups 4 (3.13±1.46 MPa) and group3 (1.44±0.96 MPa), respectively. The effect of smear layer removal on push-out bond strength of CEM was significant (P=0.01), however, it was not significant for WMTA (P=0.52). The failure mode for all the groups was of mixed type. Conclusion: Under the limitations of this study, smear layer removal is recommended for CEM in order to gain higher push-out strength.